Fair trade and staple foods: A systematic review (2020)
Sustainability certification schemes such as FAIRTRADE, FLO, WFTO and FT-USA have gained increasing markets. The significant growth of the fair trade (FT) movement in the last decades draws attention to ethical consumption. FT’s aim at improving the livelihoods of producers in developing countries and promotion of social change is considered a model that shows the benefits of trade to development. Although conveying a large number of publications, not all questions about the movement are explored. The literature is prolific on coffee, cacao, flowers, wine, and gold. In contrast, the engagement with staple foods – a prominent globally traded food category – seems minor. The primary objective of this review was to map the existing literature about FT and staple foods; then, to investigate the role of staple foods in the FT movement. The search strategy was designed to retrieve publications on the intersection of FT and staple foods. To date, there is no review about FT and staple foods nexus. Our systematic review addressed this gap considering FT as an alternative capable of addressing unsustainable food consumption and production impacts. Our research protocol included keywords searching across four databases, screening, and comparative analysis. From 283 documents retrieved, 49 were deemed relevant to reflect the role of staple foods in the FT movement. This systematic review discusses challenges and opportunities for the FT model to further engage with staples and recommends improvement of its environmental credentials. The present study can contribute by informing decision makers, policy makers, businesses, NGOs, producers, and consumers.